PET imaging reveals lower kappa opioid receptor availability in alcoholics but no effect of age. (December 2018) - Vijay, Aishwarya; Cavallo, Dana; Goldberg, Alissa; de Laat, Bart; Nabulsi, Nabeel; Huang, Yiyun; Krishnan-Sarin, Suchitra; Morris, Evan
Abstract Opioid receptors are implicated in alcoholism, other addictions, withdrawal, and depression, and are considered potential pharmacological targets for treatment. Our goal in the present study was to compare the availability of kappa opioid receptors (KOR) between an alcohol-dependent cohort (AD) and a healthy control cohort (HC). Sixty-four participants—36 AD and 28 HC—underwent PET scans with [11 C]LY2795050, a selective kappa antagonist tracer. Partial-volume correction was applied to all PET data to correct for atrophy. Volume of distribution (V T ) of the tracer was estimated regionally as a measure of KOR availability.V T values of AD versus HC were compared for 15 defined ROIs. Multivariate analysis showed a main effect of group onV T across these 15 ROIs. Post hoc tests showed that AD had significantly lowerV T and thus a lower KOR availability than HC in amygdala and pallidum (corrected for multiple comparisons). Exploratory analysis of change inV T with age was conducted;V T was not found to vary significantly with age in any region. Our findings of lowerV T in AD versus HC in multiple regions are in contrast to findings in the mu and delta opioid receptor systems of higherV T in AD versus HC. Although age-related decline in receptors has previously been observed in the mu opioid receptor system, we found that KOR availability does not change with age.